2018
DOI: 10.1051/e3sconf/20186601011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the results of the seismic profiling and WAS-96/RMS seismoacoustic active method in an assessment of the impact of the overlying coal seam edge

Abstract: In the study, a comparison between the results of seismic profiling and the active seismoacoustic method WAS-96/RMS has been presented. The methods were used to assess the impact of an overlying coal seam edge on the relative stress state of the test heading in the chosen hard coal mine in the Upper Silesian Coal Basin, Poland. The work presents the methodologies of measurement, processing and interpretation of both methods. In the research area there were two edges of the adjacent seams at vertical distances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Interesting study was conducted by Olechowski et al [12] who compared the results of seismic profiling with the results of the WAS-96/RMS method [13]. They concluded that the seismic profiling method provides more reliable results.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting study was conducted by Olechowski et al [12] who compared the results of seismic profiling with the results of the WAS-96/RMS method [13]. They concluded that the seismic profiling method provides more reliable results.…”
Section: Introductionmentioning
confidence: 99%